Offshore operations capability: a multi-case study - Tondolo, Vilmar Antonio Gonçalves (2011)
The main objective of this dissertation is to understand how companies develop capability to manage and implement offshore operations. Even though offshore operations is not a new subject – it has been practiced by companies for a long time, and is a growing operations practice employed by companies worldwide – academic efforts are still needed to achieve a full understanding of this phenomenon. One of those efforts is the comprehension of the strategic aspects of offshore. Offshore has implications for the strategic management field because it can instigate a firm to develop new capabilities and resources. In addition, companies have also moved high skill and core business activities overseas, requiring implementation of new organizational measures. For instance, literature has suggested that capabilities development is important to undertake more complex offshore processes and to overcome managerial challenges and implementation barriers. Thus, this study integrates Dynamic Capabilities as a main theory lens and offshore operations as organizational context. More specifically, this study takes Dynamic Capabilities as the “firm's ability to integrate, build, and reconfigure internal and external competences to address rapidly changing environments” (Teece, Pisano, & Shuen, 1997, p. 516). This concept emphasizes Dynamic Capabilities as a set of organizational processes, which result in the development of specific capabilities in order to fit with environmental conditions. This study also takes offshore operations as “the movement or relocation of domestic firm activities and operations abroad” (Bunyaratavej, Hahn, & Doh, 2008, p.227). Thus, the study offers a twofold contribution to the field. First, it explores how companies develop capability to manage offshore operations. Second, it explores the role of three dynamic capabilities elements (paths, positions, and processes) in the development of such capabilities. In order to achieve its objectives, eight case studies with manufacturing companies that have implemented captive offshore 6 operations were carried out. The qualitative data were collected through semi-structured interviews. The interview protocol was developed to cover elements related to dynamic capabilities and offshore based on a literature review. Using theory building through case studies, it was possible to obtain research outcomes such as types of offshore operations implemented by the companies; strategic roles of offshore operations; barriers to implement offshore operations; coordination mechanisms, resources, and capabilities developed by companies to implement offshore operations; and the role of dynamic capabilities elements (paths, positions, processes, and firm-specific DC processes) on the development of capability to manage and implement offshore operations. We also suggest propositions and an integrated model. Finally, this study contributes to practitioners by suggesting methods used by companies that have been developing capability to manage offshore operations.